ECONOMIC VALUATION OF HUMAN RESOURCES IN ACHIEVING COMPANY PERFORMANCE - Rizal Ahmad; Anggun Morizar; Miftah El Fikri (Quantitative Economics Journal, 2022)
This study aims to determine how the influence of work discipline (X1), competence (X2), and morale (X3) on the performance of employees (Y) PT. Mitra Indo Media Medan Branch. The population in this study were all employees of PT. Mitra Indo Media Medan Branch which recruited 60 employees. The number of samples taken is population of 60 respondents. This research was conducted from March to August 2020. This study used quantitative data processed by SPSS with multiple linear regression models. The results showed that work discipline, competence, and work spirit had a positive and significant effect on the performance of employees of PT. Mitra Indo Media Medan Branch either partially or simultaneously. The competency variable is the variable that most influences employee performance. 92.0% of employee performance can be explained and obtained from work discipline, competence, and work spirit, apart from other factors. employee performance has a very strong relationship to work discipline, competence, and morale.Keywords: Work Discipline, Competence, And Morale, Employee Performance.